KHULU' AND THE CONTROVERSY IN ISLAMIC LEGAL THOUGHT: THE DIVERGING PERSPECTIVES OF IMAM BAKR AL-MUZANI AND IMAM AL-SYAFI'I ON SERIOUSLY ILL WOMEN - Botutihe, Rahmad Riyansah; Misbahuzzulam (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to explore the differing opinions of Imam Bakr Al-Muzani and Imam al-Syafi'i concerning the permissibility of khulu'—a form of divorce initiated by the wife—particularly in cases where the woman is seriously ill. Given the recent viral phenomenon of khulu' leading to marital dissolution, this study seeks to provide a nuanced understanding of these classical Islamic juristic perspectives. A qualitative research design with a comparative approach was employed to investigate the subject matter. Data sources were obtained through observation, documentation, and an extensive literature review. The collected data were analyzed in a systematic manner involving selection, presentation, and conclusion-drawing phases to ensure the robustness of the findings. The findings revealed a significant divergence in the opinions of the two scholars. Imam Bakr al-Muzani opposed the majority scholarly view that considered the verse related to khulu' to be abrogated (mansukhah). Conversely, Imam al-Syafi'i maintained that khulu', including cases where the woman is seriously ill, is permissible. This difference underscores the broader debate within Islamic jurisprudence regarding the application of khulu' in contemporary contexts. This study contributes to the existing body of knowledge by highlighting the relatively underexplored opinions of Imam Bakr al-Muzani on the issue of khulu'. It also provides a comparative analysis with the more commonly referenced views of Imam al-Syafi'i, thereby enriching the discourse on women's rights in Islamic law, particularly in situations of severe illness. The research suggests that, based on the strongest opinion, women who are seriously ill may be permitted to perform khulu'. This finding has significant implications for contemporary Islamic legal practice, particularly in providing relief and legal options to women in dire health conditions seeking marital dissolution.